Memoryless logic circuit design based on the quantum phase slip junctions for superconducting digital applications - Malekpoor A.; Hashemi S.A.; Jit S. (My University, 2025)
In this article, the quantum phase slip junction (QPSJ) based full adder, multiplexer, and demultiplexer memoryless circuits for superconducting digital applications are designed for the first time. Generally, the memoryless circuits are implemented by interconnection of the basic gates (i.e., AND, OR, NOT). So in this article, the structures of the QPSJ-based AND and OR gates are also modified in order to reduce the complexity of their connections to the other gates by removing or changing the location of the clock pulse from their output branches. When a gate is connected to the next one, the elements of the second gate are loaded to the circuit of the first gate. The output current of the first gate will be affected due to this loading and no Cooper pair may be produced at its output and the next connected gate will not be switched. Therefore, the main tip in designing of these circuits is that each constituent gate must provide the necessary output current to drive the next connected gates, since each gate is driven by one Cooper pair. In this article, providing sufficient output current for each gate has been observed by 1) selecting proper critical voltages of the QPSJs and 2) by adding extra elements to or removing some elements from the connected gates in the proposed memoryless circuits. 1051-8223 © 2021 IEEE.